2022
DOI: 10.1126/sciimmunol.abo3420
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of exhausted alloreactive T cells enables targeting of stem-like memory T cells to generate tumor-specific immunity

Abstract: Some hematological malignancies such as multiple myeloma are inherently resistant to immune-mediated antitumor responses, the cause of which remains unknown. Allogeneic bone marrow transplantation (alloBMT) is the only curative immunotherapy for hematological malignancies due to profound graft-versus-tumor (GVT) effects, but relapse remains the major cause of death. We developed murine models of alloBMT where the hematological malignancy is either sensitive [acute myeloid leukemia (AML)] or resistant (myeloma)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 80 publications
(104 reference statements)
1
15
0
Order By: Relevance
“…Unexpectedly, RIP1 kinase inhibition also resulted in marked increases in T regs in GVHD target organs and the restoration of immunologic homeostasis. T cell exhaustion during GVHD has been well described ( 47 , 48 ), and GNE684 treatment reduced the expression of two T cell exhaustion markers and improved T cell functional responses to third-party alloantigens. We hypothesize that the effect of RIP1 kinase inhibition on T regs is indirect, and it is known that the reversal of dysbiosis can reduce GVHD and induce the expansion of T regs ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, RIP1 kinase inhibition also resulted in marked increases in T regs in GVHD target organs and the restoration of immunologic homeostasis. T cell exhaustion during GVHD has been well described ( 47 , 48 ), and GNE684 treatment reduced the expression of two T cell exhaustion markers and improved T cell functional responses to third-party alloantigens. We hypothesize that the effect of RIP1 kinase inhibition on T regs is indirect, and it is known that the reversal of dysbiosis can reduce GVHD and induce the expansion of T regs ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood T‐cells from post‐HCT relapsed patients expressing high PD‐1 and TIM3 were shown again to produce less IL‐2, less IFN‐γ and less TNF‐α 32 . A reduction in IFN‐γ production by CD8+ T‐cells was observed in mice with relapsed AML, further suggesting an exhausted, more terminal state of dysfunction compared to the mice in remission post‐HCT 34 . Treatment with human antibodies blocking PD‐1 led to increased T‐cell proliferation and IFN‐γ production in alloreactive T‐cell and leukaemic cell cocultures (Figure 5).…”
Section: Donor T‐cell Exhaustion As a Mechanism Of Post‐hct Relapsementioning
confidence: 96%
“…32 mice with relapsed AML, further suggesting an exhausted, more terminal state of dysfunction compared to the mice in remission post-HCT. 34 Treatment with human antibodies blocking PD-1 led to increased T-cell proliferation and IFN-γ production in alloreactive T-cell and leukaemic cell cocultures (Figure 5). 35 Strongly warranted is the establishment of a biomarker to assess T-cell exhaustion status at the time of post-HCT relapse and perhaps prior to relapse as a form of monitoring post-HCT.…”
Section: Alterations In Mhc Class I-mediated Pathways Such As Lilrbs ...mentioning
confidence: 97%
“…Galen et al showed that primitive AML cells had dysregulated transcriptional programs with co-expression of stemness and myeloid priming genes and that differentiated monocyte-like AML cells suppressed T cell activity in vitro by immunomodulatory genes [47]. Furthermore, recent advances in syngeneic models with a fully functional immune system provided opportunity to evaluate the important aspects of cancer disease progression and interactions between tumor microenvironment [48,49].…”
Section: Interactions In the Tumor Microenvironmentmentioning
confidence: 99%
“…When and how to combine allo-HSCT with adoptive immunotherapy in AML is still debated. The mechanisms of resistance to T cell-mediated antitumor effects after allo-HSCT are well-defined in sophisticated murine models of allo-HSCT [142]. Combining a novel myeloablative irradiationbased conditioning regimen with regulatory and conventional T cell immunotherapy in haploidentical transplantation was shown to eradicate AML [143].…”
Section: Allogeneic Hematopoietic Stem Cell Transplantation With Car ...mentioning
confidence: 99%